PENGARUH FIRM SIZE TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2004-2009 - Mar'ati, Fudji Sri (AMONG MAKARTI, 2013)
Abstract This research is performed in order to analyze the influence between Firm Size and Stock Return of the Manufacture Industry was listed in Indonesian Directory Exchange (IDX). Methodology research as the sample used purposive sampling. Data that needed in this research from Indonesian Capital Market Directory ( ICMD) and total sample was acquired 20 industry. Data analysis with regression. Empirical evidence show Firm Size to have negative influence with Stock Return.   Keyword :  Firm Size, Stock Return